2016
DOI: 10.21273/hortsci10706-16
|View full text |Cite
|
Sign up to set email alerts
|

No Tillage and Strip Tillage Effects on Plant Performance, Weed Suppression, and Profitability in Transitional Organic Broccoli Production

Abstract: Organic no-till and strip-till systems have gained attention because of their reported capacity to enhance soil health and suppress annual weeds. This study, conducted at the Horticulture Research Station, Ames, IA, over 2 years (2013–14 and 2014–15) compared a cover crop–based no tillage (NT), strip tillage (ST), and conventional tillage (CT) in transitional organic broccoli (Brassica oleracea L. var. italica) production, with data collected on bro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Studies that specifically compared tillage system effects on CC biomass production reported that tillage method did not generally affect CC biomass production in 20 of 22 studies using a variety of CC species including radish, hairy vetch, and rye (Yaffa et al, 2000;Sainju et al, 2005;Schomberg et al, 2006;Petersen et al, 2011;Evans et al, 2016). One of the two remaining studies found that CC biomass was 2.3 Mg ha -1 greater with strip till and 0.8 Mg ha -1 lower with conventional tillage compared to no-till (Jokela and Nair, 2016), while the other study found that tillage had variable effects ranging from neutral to increased biomass production (Price et al, 2016). Our review suggests that CC biomass production may not depend on tillage in most studies, which is somewhat surprising because tillage can move crop residues below the soil surface and can improve seed-soil contact compared to no-till.…”
Section: Tillage Methodsmentioning
confidence: 99%
“…Studies that specifically compared tillage system effects on CC biomass production reported that tillage method did not generally affect CC biomass production in 20 of 22 studies using a variety of CC species including radish, hairy vetch, and rye (Yaffa et al, 2000;Sainju et al, 2005;Schomberg et al, 2006;Petersen et al, 2011;Evans et al, 2016). One of the two remaining studies found that CC biomass was 2.3 Mg ha -1 greater with strip till and 0.8 Mg ha -1 lower with conventional tillage compared to no-till (Jokela and Nair, 2016), while the other study found that tillage had variable effects ranging from neutral to increased biomass production (Price et al, 2016). Our review suggests that CC biomass production may not depend on tillage in most studies, which is somewhat surprising because tillage can move crop residues below the soil surface and can improve seed-soil contact compared to no-till.…”
Section: Tillage Methodsmentioning
confidence: 99%
“…Shank and coulter ST equipment, as used in our trials, can lead to rough and nonuniform seedbed conditions when operating in grass crowns and present challenges for crop establishment (Luna & Staben, 2002). Others have used an additional ST pass in late fall after cover crop establishment to reduce interference with spring ST at the time of cash crop planting (Jokela & Nair, 2016a). The ST and planting tools used and crop type (direct seeded vs. transplanted) could be important considering this potential advantage of segregated plantings.…”
Section: Mixture and Spatial Arrangement Effects On Cover Crop Biomassmentioning
confidence: 99%
“…capitata ) (Haramoto & Brainard, 2012; Hefner et al., 2020), broccoli ( Brassica oleracea var. italica ) (Jokela & Nair, 2016a), bell pepper ( Capsicum annuum L.) (Delate et al., 2008; Jokela & Nair, 2016b), sweet corn ( Zea mays L.) (Lowry & Brainard, 2017), cucurbits, and others (Leavitt et al., 2011; Lilley & Sanchez, 2016). Reduced N availability under RT is variously attributed to temperature and moisture mediated reductions in N mineralization rates (Dou et al., 1994; Grandy & Robertson, 2006), increases in N 2 0 emissions (MacKenzie et al., 1997), increased volatilization of surface‐applied fertilizers when not incorporated, and/or immobilization of N in surface residues (Grandy et al., 2006; Ismael et al., 1994; Mulvaney et al., 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In these systems, cover crops are terminated without incorporating residues into the soil, thus leaving a thick mulch into which the subsequent cash crop is planted. This requires the necessity to produce large cover crop biomass as well as a good management of their residues to provide maximum weed suppression and nutrients adjustments, e.g., reduce immobilization, enhance N release and synchronization with plant needs [9]. Weed management and nutrient availability are two factors known to challenge the performance of crops in organic no-till production.…”
Section: Introductionmentioning
confidence: 99%